THE EFFECT OF BUREAUCRATIC SIMPLIFICATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AND CAREER DEVELOPMENT AS INTERVENING VARIABLES AT BPS JAWA TIMUR PROVINCE - Ulum, Bahrul; Nur, Dhani Ichsanuddin (UNIVERSITAS PAKUAN, 2025)
This study aims to examine the effect of bureaucratic simplification on employee performance with job satisfaction and career development as intervening variables at the Central Statistics Agency (BPS) of Jawa Timur Province. The research method is applied with a quantitative approach through Structural Equation Modeling analysis. The population in the study was the team leader at the Central Statistics Agency throughout Jawa Timur with a sample of 217 employees. Primary data collection was carried out using an online questionnaire distributed to respondents. The results of the study concluded that bureaucratic simplification has been implemented within the scope of the BPS of Jawa Timur Province but has not provided an optimal performance impact and requires further adjustments to achieve the expected results. Bureaucratic simplification has a major impact on employee performance through the level of job satisfaction. Bureaucratic simplification has the potential to improve performance through career development, but still requires a number of improvements in its implementation, especially in terms of socialization and improvement of the mutation or job rotation system.